2018
DOI: 10.2355/isijinternational.isijint-2017-537
|View full text |Cite
|
Sign up to set email alerts
|

Randomization of Ferrite/austenite Orientation Relationship and Resultant Hardness Increment by Nitrogen Addition in Vanadium-microalloyed Low Carbon Steels Strengthened by Interphase Precipitation

Abstract: Interphase precipitation of nano-sized alloy carbides is recently used to strengthen low carbon steels for its excellent contributions to strength and formability. The effects of nitrogen addition on the hardness of vanadium-microalloyed low carbon steels were investigated by considering both the dispersion of interphase precipitation and the ferrite/austenite crystallography. Three-dimensional atom probe analysis reveals that interphase precipitation of vanadium carbide is hardly affected by increasing the ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…4e) shows the same tendency as that in number density, indicating that higher hardness of a can be obtained by more dispersed VC interphase precipitation. 56 It should be mentioned that these data also include some cases of GBF holding a near K-S OR, which means that the dispersion of interphase precipitation and resultant hardening effects are actually determined by a/c OR rather than by the morphology of a. The occurrence of interphase precipitation in planar sheets at the a/ c interface with a non-K-S OR suggests that, even when the a/c OR largely deviates from the rational K-S OR, the macroscopic a/c interface should be composed of some partially coherent crystal planes in local regions, the mobility of which is sufficiently low to enable the nucleation of alloy carbides at the interface, 57 whereas, in some special cases when the degree of coherency is not sufficiently low, irregular or even random dispersion of alloy carbides rather than planar sheets might also be formed.…”
Section: Effects Of A/c Orientation Relationship On the Dispersion Of Interphase Precipitationmentioning
confidence: 99%
“…4e) shows the same tendency as that in number density, indicating that higher hardness of a can be obtained by more dispersed VC interphase precipitation. 56 It should be mentioned that these data also include some cases of GBF holding a near K-S OR, which means that the dispersion of interphase precipitation and resultant hardening effects are actually determined by a/c OR rather than by the morphology of a. The occurrence of interphase precipitation in planar sheets at the a/ c interface with a non-K-S OR suggests that, even when the a/c OR largely deviates from the rational K-S OR, the macroscopic a/c interface should be composed of some partially coherent crystal planes in local regions, the mobility of which is sufficiently low to enable the nucleation of alloy carbides at the interface, 57 whereas, in some special cases when the degree of coherency is not sufficiently low, irregular or even random dispersion of alloy carbides rather than planar sheets might also be formed.…”
Section: Effects Of A/c Orientation Relationship On the Dispersion Of Interphase Precipitationmentioning
confidence: 99%
“…In addition, K–S OR has 24 possibilities. Hence, though significant amount of α‐ferrite nucleation was considered having K–S OR with austenite, [ 35 ] the misorientation angle between FPAGB and δ‐ferrite could be considered random. However, since the FIADF and δ‐ferrite belong to the same ferrite grain, the orientation of FIADF and δ‐ferrite was almost the same.…”
Section: Resultsmentioning
confidence: 99%
“…Precipitation strengthening is an effective approach to increase the strength of steels and has received significant attention. Since its discovery in the 1960s [ 1 ], interphase precipitation has been an important form of precipitation and of particular interest to researchers [ 2 , 3 , 4 ]. Studies have shown that a number of precipitate-forming elements can form interphase precipitation, such as carbonitrides of Ti, Nb, V, Mo, Cr, etc.…”
Section: Introductionmentioning
confidence: 99%